Evaluasi Dampak Kebijakan Instrumen Akreditasi 2020 pada Satuan Pendidikan Pendidikan Dasar Menengah di Provinsi Banten - Jumanah; Arif Nugroho; Dine Trio Ratnasari; Pryo Handoko (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
This research aims to evaluate the impact of the 2020 Accreditation Instrument policy on the improvement of education quality in primary and secondary education units in Banten Province using the context, input, process, and product (CIPP) evaluation framework. The approach used is descriptive qualitative strengthened by quantitative data. Data collection was conducted thru in-depth interviews, questionnaires, observations, and documentation studies involving school principals, teachers, and educational stakeholders. Data analysis was conducted interactively thru reduction, presentation, and conclusion drawing, and was reinforced with thematic analysis assisted by NVivo software. The research results indicate that in the context dimension, this policy is relevant to the need for a more objective and performance-based accreditation system reform, although the understanding among implementers is not yet uniform. In the input dimension, the availability of resources is relatively adequate, but there are still disparities in human resource competence, infrastructure, and access to training and mentoring. In the process dimension, policy implementation has increased transparency, efficiency, and objectivity thru digital systems, although it still faces challenges in technology literacy and variations in indicator interpretation. In the product dimension, this policy has a positive impact on improving the quality of learning, strengthening school governance, and fostering a culture of quality, but its impact is not yet evenly distributed across regions. Overall, the 2020 Accreditation Instrument is a strategic policy in improving the quality of education, but it requires continuous strengthening thru capacity building, equitable access, and optimization of policy implementation to make its impact more effective and sustainable.